1998
DOI: 10.1212/wnl.50.1.301
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis and hypoxia associated with prolonged propofol infusion in children

Abstract: Propofol, a new anesthetic, is now used more commonly to sedate patients in the intensive care unit. Propofol's rapid elimination has popularized its use to induce and maintain hypnosis in patients with refractory status epilepticus. It is also associated with occasional severe metabolic acidosis and hypoxia of indeterminate cause in children. We report a child and an adolescent who developed severe metabolic acidosis, progressive hypoxia, and rhabdomyolysis during maintenance infusion of propofol for the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(72 citation statements)
references
References 4 publications
0
61
0
11
Order By: Relevance
“…Nesses casos, a eletroneuromiografia está indicada para o diagnóstico de lesão muscular ou neurológica 22 . Arabdomiólise em crianças pode estar associada a musculopatias hereditárias, hipertermia maligna e a síndrome da infusão contínua de propofol, sendo comum a parada cardíaca por hiperpotassemia 4, [25][26][27][28] . O caso paciente pediátrico relatado não apresentou sinais de hipermetabolismo durante a anestesia, tinha história negativa para musculopatias e não recebeu propofol.…”
Section: Discussionunclassified
“…Nesses casos, a eletroneuromiografia está indicada para o diagnóstico de lesão muscular ou neurológica 22 . Arabdomiólise em crianças pode estar associada a musculopatias hereditárias, hipertermia maligna e a síndrome da infusão contínua de propofol, sendo comum a parada cardíaca por hiperpotassemia 4, [25][26][27][28] . O caso paciente pediátrico relatado não apresentou sinais de hipermetabolismo durante a anestesia, tinha história negativa para musculopatias e não recebeu propofol.…”
Section: Discussionunclassified
“…El propofol ha sido usado en anestesia durante más de 20 años y ha demostrado tener un buen perfil de seguridad 2 . Sin embargo, varios reportes han advertido sobre los peligros de su administración en altas dosis y por tiempo prolongado, tanto en niños [3][4][5][6][7][8] como en adultos [9][10][11][12][13] .…”
unclassified
“…Antihistamines, anesthetics, and amphetamines have recently been implicated as the etiology of drug-induced rhabdomyolysis in several pediatric patients (1,2,7,8). Hanna et al reported a child who developed severe metabolic acidosis, progressive hypoxia, and rhabdomyolysis during a maintenance infusion of propofol for the treatment of refractory status epilepticus (9). The occurrence of rhabdomyolysis after ingestion of an overdose of isoniazid in a 17-year old girl who recovered completely has also been reported (10).…”
Section: Discussionmentioning
confidence: 99%